PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (Studi pada PT Banjar Elektronika Sarana Televisi) - Herlina Lusiana; Firdaus - (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, The purpose of this study are : (1) To analyze and test the effect of partial compensation on employee performance; (2) To analyze and test the effect of work motivation partially on employee performance; (3) To analyze and test the effect of compensation and work motivation simultaneously on employee performance. This research was conducted at PT Banjar Elektronika Television facilities. There are 26 respondents who have been selected as samples using the slovin formula and saturated sampling technique. Research method using survey mthod and research type is quantitative research. While the nature of this reserach including explanatory reserach (explanatory research). Methods of data collection using questionnaires, while the data analysis techniques using hypothesis testing using SPSSprogram IBM version 21. The results showed that compensation (X1) did not have a partial effect on employee performance at PT Banjar Elektronika means Television, work motivation (X2) has a partial influence at PT Elektronika means Television facilities an compensation (X1) dan work motivation (X2) has no effect simultaneously on the performance of employees at PT Banjar Elektronika Television.